1994
DOI: 10.1172/jci117277
|View full text |Cite
|
Sign up to set email alerts
|

Effects of chronic beta-adrenergic blockade on the left ventricular and cardiocyte abnormalities of chronic canine mitral regurgitation.

Abstract: The mechanism by which ft blockade improves left ventricular dysfunction in various cardiomyopathies has been ascribed to improved contractile function of the myocardium or to improved ,8-adrenergic responsiveness. In this study we tested two hypotheses: (a) that chronic 13 blockade would improve the left ventricular dysfunction which develops in mitral regurgitation, and (b) that an important mechanism of this effect would be improved innate contractile function of the myocardium.Two groups of six dogs with c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
116
2
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 170 publications
(127 citation statements)
references
References 57 publications
8
116
2
1
Order By: Relevance
“…␤-Blockade improves LVEF by biologically augmenting myocyte and chamber contractility. [1][2][3][4] This improvement does not occur immediately but rather between 1 and 3 months of therapy. 3 A partial explanation of biological improvement in LVEF may be upregulation of sarcoplasmic reticulum calcium ATPase (SERCA2), a protein that controls calcium sequestration, and an increase in the relative amount of ␣-myosin heavy chain.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…␤-Blockade improves LVEF by biologically augmenting myocyte and chamber contractility. [1][2][3][4] This improvement does not occur immediately but rather between 1 and 3 months of therapy. 3 A partial explanation of biological improvement in LVEF may be upregulation of sarcoplasmic reticulum calcium ATPase (SERCA2), a protein that controls calcium sequestration, and an increase in the relative amount of ␣-myosin heavy chain.…”
Section: Discussionmentioning
confidence: 90%
“…[1][2][3][4] This results in improved ventricular function, an increase in myocardial chamber efficiency, and a reversal in the pathological remodeling process. [1][2][3][4] In many cases, this translates into a survival benefit, [5][6][7][8] but in the BEST study, there was no clear survival benefit, despite an improvement in left ventricular ejection fraction (LVEF) with bucindolol. 9 However, not all patients have improved LVEF with ␤-blocker therapy.…”
mentioning
confidence: 99%
“…Myocardial systolic or diastolic dysfunction accrues from histopathologic changes that cause myocardial decompensation, which in turn induces clinical signs such as cough, dyspnea, and exercise intolerance 3, 4, 8, 9, 10. However, knowledge is incomplete regarding the pathologic progression of myocardial degeneration and attendant difficulties in evaluating myocardial dysfunction in DMVD.…”
Section: Discussionmentioning
confidence: 99%
“…Because the clinical signs of DMVD develop slowly over a period of years, they are often recognized only after cardiac remodeling has already occurred 19. Several studies in dogs with experimentally induced mitral valve insufficiency showed severe myocardial degeneration (e.g., myofibrillar loss, increased perinuclear space, and hypertrophy) in the LV as early as 4 months after induction of mild mitral regurgitation 10, 20, 21. Similarly, apoptosis of cardiac myocytes was detected before ventricular hemodynamic impairment or systolic dysfunction in experimental dogs with ventricular pacing 22.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation